Linguistic Capital and Symbolic Violence: A Phenomenological Analysis of Foreign Nationals in Indonesian Housing - Nurul Huda; Engkus Kuswarno; Ilham Gemiharto (Balai Bahasa Provinsi Bali, 2026)
Foreign nationals residing in Indonesian local housing face structural linguistic disadvantages that existing second language acquisition literature has largely overlooked, particularly in non-institutional everyday settings. This study aims to analyze how linguistic capital and symbolic violence operate in shaping the identity reconstruction of foreign nationals within an Indonesian residential context. This research employs a critical phenomenological approach integrating Bourdieu’s linguistic capital theory with Schutz’s social phenomenology. Data were drawn from semi-structured in-depth interviews (60–90 minutes) with six foreign nationals residing at Easton Park Apartment, Jatinangor, representing diverse linguistic backgrounds (Kenya, China, Pakistan, England, Ethiopia, and Bangladesh), as well as the apartment manager. Data were collected through purposive and maximum variation sampling, then analyzed through phenomenological reduction combined with critical discourse analysis. Findings reveal that linguistic identity awareness emerges through systematic communicative breakdown across phonological, morphosyntactic, and pragmatic dimensions. Foreign nationals deploy four adaptive strategies: technological mediation, gestural compensation, practical mimesis, and code-switching. These strategies, how-ever, operate within asymmetrical power relations that produce symbolic violence through the systematic misrecognition of non-native competence—a condition this study terms “linguistic precarity.” Identity reconstruction unfolds across four temporal phases, from existential disorientation to hybrid linguistic integration, yet competence remains situationally fragile. Critically, the study exposes institutional linguistic violence through the complete absence of linguistic support structures at the residential level, forcing individualized adaptation without systemic scaffolding. These findings carry significant implications for housing policy, institutional linguistic justice, and critical language pedagogy, calling for multilingual support systems that recognize linguistic diversity as a communal resource rather than an individual deficiency. AbstrakWarga negara asing yang tinggal di hunian lokal Indonesia menghadapi ketimpangan linguistik struktural yang selama ini kurang mendapat perhatian dalam literatur pemerolehan bahasa kedua, khususnya dalam konteks keseharian di luar institusi formal. Penelitian ini bertujuan menganalisis bagaimana modal linguistik dan kekerasan simbolik beroperasi dalam membentuk rekonstruksi identitas warga negara asing di lingkungan hunian Indonesia. Penelitian ini menggunakan pendekatan fenomenologi kritis yang mengintegrasikan teori modal linguistik Bourdieu dengan fenomenologi sosial Schutz. Data diperoleh melalui wawancara mendalam semi-terstruktur (60–90 menit) dengan enam warga negara asing yang bermukim di Easton Park Apartment, Jatinangor, yang mewakili latar belakang linguistik beragam (Kenya, Cina, Pakistan, Inggris, Ethiopia, dan Bangladesh), serta pengelola apartemen. Pengumpulan data dilakukan melalui purposive sampling dengan variasi maksimum, kemudian dianalisis menggunakan reduksi fenomenologis yang dipadukan dengan analisis wacana kritis. Hasil penelitian menunjukkan bahwa kesadaran identitas linguistik muncul melalui kegagalan komunikatif sistematis yang meliputi dimensi fonologis, morfosintaktis, dan pragmatis. Warga asing menerapkan empat strategi adaptif: mediasi teknologi, kompensasi gestural, mimesis praktis, dan alih kode. Namun, strategi-strategi ini beroperasi dalam relasi kuasa yang asimetris dan melahirkan kekerasan simbolik melalui salah pengakuan (misrecognition) kompetensi non-penutur asli—kondisi yang dalam penelitian ini disebut sebagai “prekaritas linguistik.” Rekonstruksi identitas berlangsung melalui empat fase temporal, dari disorientasi eksistensial hingga integrasi linguistik hibrida, namun kompetensi yang dicapai tetap bersifat situasional dan rentan. Secara kritis, penelitian ini mengungkap kekerasan linguistik institusional melalui ketiadaan total dukungan linguistik di tingkat hunian, yang memaksa warga asing menjalani adaptasi secara individual tanpa dukungan terstruktur. Temuan ini memiliki implikasi signifikan bagi kebijakan perumahan, keadilan linguistik institusional, dan pedagogi bahasa kritis, dengan mendesak penerapan sistem dukungan multibahasa yang mengakui keragaman linguistik sebagai sumber daya kolektif, bukan beban yang harus ditanggung sendiri oleh individu.